Circulating memory B-cell receptor repertoire analysis identifies novel candidate antibodies against metastatic melanoma in immunotherapy-responsive patients - Nicolini, Fabio; Gaimari, Anna; Mazzotti, Lucia; De Lucia, Anna; Ghirelli, Miriana; Ancarani, Valentina; Borges de Souza, Patricia; Zurlo, Matteo; Gazzola, Luca; Magnoni, Chiara; Capobianco, Simona; Angeli, Davide; et al. (Frontiers in Immunology, 2025)
BackgroundBy examining the B-cell receptor (BCR) repertoire of metastatic melanoma (MM) patients with favorable treatment outcomes, it is now possible to identify unique patterns of immune responses, with the potential of discovering novel antitumor antibodies.MethodsHere, we isolated CD27-positive circulating memory B cells from non responders, partial responders, and complete responders MM patients to first-line therapy with anti-PD-1 immune checkpoint inhibitor (ICI) nivolumab, to perform a BCR repertoire sequencing analysis. We looked for complementarity-determining region 3 (CDR3) sequences that were enriched (de novo formed) following ICI treatment. Fully-human immunoglobulins were then produced in Expi293F™ cells using CDR3-sequencing information and tested for specificity and sensitivity on different MM cell lines and patient-derived xenograft cells by flow cytometry and by immunohistochemistry on human tissue microarrays.ResultsAs a result of immunotherapy stimulation in responder patients, we observed that some CDR3 clonotypes have emerged de novo. Among the nine candidate antibodies we assessed, two antibodies exhibited encouraging tumor-targeting properties, although they also showed a degree of cross-reactivity with normal skin and melanocytes.ConclusionsAlthough our study is based on a limited number of individuals, our observations indicate that it may be possible to further investigate the human response to immunotherapy for the identification of rare mature B clonotypes targeting plasma membrane antigens on tumor cells. These preliminary findings could contribute to the future development of fully human-compatible immunotherapies, pending additional validation and in vivo studies.